CONTINUING PHARMACYEDUCATION SERIES-RISK FACTORS AND COMPLICATIONS OF DIABETES - SHEEJAV S; HARIKRISHNA REDDYM; JIBIN C JOSEPH; KRISHNA RAJ R (International Journal of Pharma and Bio Sciences, 2010)
Diabetic is a complex metabolic condition that requires meticulous management and a global approach. Poor management and control of diabetes often lead to poor disease outcomes. The management of diabetes and its complications presents an increasing challenge to health care systems throughout the world. New findings regarding complications of diabetes, their prevalence and incidence, and risk factors involved were discussed in this paper. Various risk factors associated with diabetes include-diabetic neuropathy, diabetic retinopathy, hypoglycemia, metabolic syndrome, T.B musculoskeletal disease, hypoglycemia, Chronic liver disease and coronary heart disease, Foot ulcers and amputations, mental function and dementia, infections, depression and changes in bone quality1. So, prevention of diabetes will need deeper understanding by the patients and their surroundings before medical advancements throw up a magical cure to it. Pharmacist can play an important role by screening patients at higher risk for diabetes, assessing patient health status and adherence to standards of care, patient education referring patients to other health care professionals as appropriate for other complications monitoring the outcomes2. A buildup of awareness and high motivation levels among society as a whole will ensure active co-operation of every individual for a healthy living.